1992
DOI: 10.1095/biolreprod46.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Insulin-Like Growth Factor-I (IGF-l) and its Receptor in the Peri-Implantation Mouse Uterus, and Cell-Specific Regulation of IGF-l Gene Expression by Estradiol and Progesterone1

Abstract: This study describes the expression of insulin-like growth factor-I (IGF-I) and IGF-I receptor (IGF-IR) genes in the mouse uterus during the peri-implantation period (Days 1-6 of pregnancy), as well as effects of estradiol (E) and progesterone (P) on cell-specific IGF-I gene expression in the uterus of the ovariectomized adult mouse. Northern blot analysis showed that IGF-I mRNA levels were low but readily detectable in the uterus on Day 1 of pregnancy and steadily increased, reaching high levels just before (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
104
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(119 citation statements)
references
References 0 publications
12
104
0
3
Order By: Relevance
“…Estrogen stimulates Igf1 transcription (Murphy et al, 1987;Ghahary et al, 1990;Kapur et al, 1992;Zhou et al, 1994;Ohtsuki et al, 2005), and high levels of circulating estrogen at proestrus induced high Igf1 mRNA levels. Igf1r mRNA levels also changed during the estrous cycle; they were high at diestrus and low during proestrus and estrus, suggesting that the responsiveness of endometrial cells to IGF1 depends upon the stage of the estrous cycle, and possibly upon levels of estrogen and progestin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen stimulates Igf1 transcription (Murphy et al, 1987;Ghahary et al, 1990;Kapur et al, 1992;Zhou et al, 1994;Ohtsuki et al, 2005), and high levels of circulating estrogen at proestrus induced high Igf1 mRNA levels. Igf1r mRNA levels also changed during the estrous cycle; they were high at diestrus and low during proestrus and estrus, suggesting that the responsiveness of endometrial cells to IGF1 depends upon the stage of the estrous cycle, and possibly upon levels of estrogen and progestin.…”
Section: Discussionmentioning
confidence: 99%
“…The steroid hormone-induced proliferation of endometrial cells is thought to be mediated by growth factors produced in endometrial stromal cells (Tomooka et al, 1986;DiAugustine et al, 1988;Beck and Garner, 1992;Das et al, 1994;Cooke et al, 1997). Insulin-like growth factor 1 (IGF1) is expressed in all components of the mouse uterus and its expression is regulated by estrogen (Murphy et al, 1987;Ghahary et al, 1990;Kapur et al, 1992;Ohtsuki et al, 2007). Moreover, IGF1 promotes the proliferation of endometrial cells (Shiraga et al, 1997;Sato et al, 2002;Inoue et al, 2005;Zhu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, delays or deficiencies in progesterone release also affected the viability of the recovered embryos. Prior authors have described the role of both hormones, oestradiol and progesterone, on the expression of several growth factors, mainly IGF on the oviduct and uterine secretions [34][35][36][37]. Although there are no studies on superovulated ewes, the presence of IGF and its binding proteins during the early embryo development, from 1 cell to the blastocyst, suggests an important role of these peptides [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…EGF and insulin-like growth factor (IGF)-I stimulate cell proliferation in immature mouse uterine and vaginal epithelial cells in vitro (Tomooka et al 1986, Iguchi et al 1987, Shiraga et al 1997. Because estrogen stimulates uterine epithelial cell proliferation (McCormack & Glasser 1980, Quarmby & Korach 1984 and expression of EGF, IGF-I, heparin-binding EGF-like growth factor, transforming growth factor (TGF)-and EGF-R in the reproductive tracts of mice and rats, these growth factors may mediate the estrogen-induced proliferative and differentiative responses in rodent reproductive tracts (Murphy et al 1987, DiAugustine et al 1988, Nelson et al 1991, Beck & Garner 1992, Ignar-Trowbridge et al 1992, Kapur et al 1992, Das et al 1994, Sahlin et al 1994, Zhang et al 1994, Falck & Forsberg 1996, Hom et al 1998. In the fetal reproductive tract, expression of EGF-R in mice (Bossert et al 1990), and EGF, TGFand IGF-I in rats (Koike & Noumura 1993, Kanno et al 1994, Gu et al 1999) was reported.…”
Section: Discussionmentioning
confidence: 99%